Glia: guardians, gluttons, or guides for the maintenance of neuronal connectivity?. (9th March 2015) - Jebelli, Joseph; Su, Wei; Hopkins, Stephanie; Pocock, Jennifer; Garden, Gwenn A.
Abstract : An emerging aspect of neuronal–glial interactions is the connection glial cells have to synapses. Mounting research now suggests a far more intimate relationship than previously recognized. Moreover, the current evidence implicating synapse loss in neurodegenerative disease etiology is overwhelming, but the role of glia in the process of synaptic degeneration has only recently been considered in earnest. Each main class of glial cell, including astrocytes, oligodendrocytes, and microglia, performs crucial and multifaceted roles in the maintenance of synaptic function and excitability. As such, aging and/or neuronal stress from disease‐related misfolded proteins may involve disruption of multiple non‐cell‐autonomous synaptic support systems that are mediated by neighboring glia. In addition, glial cell activation induced by injury, ischemia, or neurodegeneration is thought to greatly alter the behavior of glial cells toward neuronal synapses, suggesting that neuroinflammation potentially contributes to synapse loss primarily mediated by altered glial functions. This review discusses recent evidence highlighting novel roles for glial cells at neuronal synapses and in the maintenance of neuronal connectivity, focusing primarily on their implications for neurodegenerative disease research.